The influence of the AI Act on the achievement of the UN Sustainable Development Goal 3: Regulating AI for better health outcomes? - Greser, Jarosław (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
The article assesses the influence of the Artificial Intelligence Act (AI Act) on the potential for achieving the health-related aims of Sustainable Development Goal 3 (SDG 3) from an EU law perspective. Although the impact of AI on health has been widely studied, the implications of the AI Act in this regard remain underexplored in academic literature. The influence of the new regulation on research and drug development is important in the context of SDG 3. A review of existing normative acts leads to the following conclusions. Firstly, the SDGs do not possess the status of binding acts within EU lawmaking. However, their objectives are included in policy and strategy documents and thus exert indirect influence on the EU legal order. Secondly, the AI Act does not contain a direct reference to the SDGs, despite a legislative-stage proposal by Parliament. Furthermore, the issue of sustainable development is mentioned only in passing. However, the incorporation of the SDGs into policy documents precludes any interpretation of the AI Act that would impede their attainment. This is significant in the context of the AI Act’s direct impact on SDG 3, concerning prohibited practices such as profiling and scoring employed in health insurance risk assessment. A comparable situation arises regarding the indirect impact of the Act, as exemplified by its use in drug development. An interpretation aligned with the SDGs suggests that the research exemption set out in the AI Act should extend to any entity engaged in research, irrespective of its legal status.